2-(1-Pyrenyl) benzimidazole as a ratiometric and "turn-on" fluorescent probe for iron(iii) ions in aqueous solution. Issue 7 (22nd February 2016) - Zhao, Meili; Deng, Zhifu; Tang, Jian; Zhou, Xiufen; Chen, Zhi; Li, Xutian; Yang, Liting; Ma, Li-Jun
Abstract : A fluorescent probe for Fe 3+, 2-(1-pyrenyl) benzimidazole (L ), was synthesized. In aqueous solution, L shows a highly selective and sensitive ratiometric probe for Fe 3+ in emission spectra, and it can also be used as a fluorescent "turn-on" probe for Fe 3+ in excitation spectra. Abstract : A highly selective and sensitive ratiometric and "turn-on" fluorescent probe for Fe 3+, 2-(1-pyrenyl) benzimidazole (L ), was synthesized by a one-step process. In emission spectra, the relative intensity ratio of excimer to monomer fluorescence ( I E450 / I M387 ) ofL increased 510-fold upon the addition of 30 equiv. of Fe 3+ with a detection limit of 0.2 μM (11.2 ppb) in aqueous solution. Meanwhile, the fluorescence excitation spectra ofL showed a fluorescent "turn-on" probe for Fe 3+ with 30-fold enhancement in excitation band intensity of excimer.